SHOPI (Sosialisasi Pencegahan Hipertensi): Building Community Resilience Against Hypertension in Banyuwangi, Indonesia - Hayuningtuti, Faradila Nur Eka Nanda; Mandagi, Ayik Mirayanti; Alfayad, Afan (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
This community service was aimed at increasing knowledge to prevent hypertension by utilizing the role of mother cadres of PKK, which stands for Pemberdayaan dan Kesejahteraan Keluarga, a hamlet/village-level association focusing on family welfare and empowerment. These cadres are representatives of neighborhood associations (RT/Rukun Tetangga) in the village area. This community empowerment was held through counseling lectures. This activity was carried out in 2022; the data, which were the participants’ responses, were collected using pretest and post-test questionnaires. The sampling was carried out using accidental sampling with a cross-sectional design. This activity targeted 30 PKK mothers as representatives from each neighborhood in Karangrejo Village, Banyuwangi Regency. This empowerment increased the knowledge of the target community regarding the prevention of hypertension by 22.7 points. The average score of the participants’ pretest was 52.26, and that of the post-test was 74.96. This is in line with studies that found that community service activities carried out using the roles of cadres and the elderly showed optimal results in increasing the target communities’ knowledge in the operation of tensimeters and measuring blood sugar, uric acid, and cholesterol as well as increasing knowledge of cadres and the elderly in hypertension management, and dietary management of hypertension. The SHOPI Project (Education on Hypertension Prevention) eﬀectively enhances public awareness regarding hypertension prevention, with a focus on women from the PKK community in Karangrejo Village, Banyuwangi Regency.